A 'CURRENT TOPICS' COURSE IN THE ACCOUNTING CURRICULUM? - Kemp, Patrick S. (The Accounting Review, 1963)
Abstract At the May, 1961 meeting of the South-eastern Section of the American Accounting Association, it was the author's privilege to participate in a panel presentation entitled "Teaching Current Accounting Theory at the Undergraduate Level." The discussion centered around the inclusion in accounting curricula of topics receiving current attention in accounting literature, such as accounting for long-term leases, "direct" costing, and "deferred" income tax liability. This paper represents a distillation of some of the more important ideas presented and discussed at that session. There was general agreement as to the propriety of including current topics in college and university accounting programs. The study of current accounting topics certainly has a place in college and university accounting curricula. Treatment of these topics in a separate course is feasible only in institutions with broad, diversified accounting programs. Even in such schools, the desirability of such a course is open to question. The approach to teaching current accounting topics depends in large part on the basic objectives of the accounting program in each college and university.